SCHOOL-BASED EXTRACURRICULAR ACTIVITIES IMPROVE REPRODUCTIVE HEALTH KNOWLEDGE FOR HIGH SCHOOL STUDENTS: A STUDY IN TRA VINH PROVINCE, VIETNAM - Hong Hanh, Nguyen Thi (Ethiopian Journal of Reproductive Health, 2023)
ABSTRACT BACKGROUND: Reproductive health (RH) knowledge of high school students in Vietnam is poor. This study aimed to assess the effectiveness of school-based extracurricular activities in improving the RH knowledge for students in Tra Vinh province. METHODS: A pilot intervention study was conducted on the control group (70 students) who had no the extracurricular activities on RH, and the intervention group (71 students) who participated extracurricular activities on RH with two sessions (90 minutes/session). Two forms of questionnaires were used for assessing student’s level of knowledge change about RH that were built by researchers of the Department of Human and Animal Physiology, Biology Faculty, Hanoi National University of Education and evaluated by the Centre for RH Education and Family Planning. RESULTS: There was no statistically significant difference in the pre-intervention test scores between the two groups (P = 0.319) while the post-intervention scores of the intervention group and control group were 7.11 and 5.77, respectively (P = 0.026). After adjusting for age, gender, ethnicity, participation in extracurricular activities still had a statistically significant relationship with students' scores (OR = 2.96, ? = 1.09, P = 0.009). After participating in extracurricular activities, RH knowledge of students in the intervention group was dramatically improved. CONCLUSION: High school students in Tra Vinh lacked school-based extracurricular activities in RH, therefore, their RH knowledge was still limited. Extracurricular activities provided students with accurate information and knowledge of RH. KEYWORDS: Extracurricular Activities, Reproductive Health Education, High school Students, Vietnam